MARKETING STRATEGY FOR THE RESULTS OF BATIK JERUJI INDEPENDENCE DEVELOPMENT IN CLASS IIA CORRECTIONAL INSTITUTION BANYUWANGI - Lucky Hari Yulinarto; Vivi Sylviani Biafri (Universitas Nusa Cendana, 2026)
Batik Jeruji is a product created by inmates through self-reliance development activities at Class IIA Banyuwangi Correctional Institution. Despite having unique motifs and good product quality, the marketing of Batik Jeruji still faces several challenges. The product is not widely known by the public, and its marketing mainly relies on the prison gallery and word-of-mouth promotion. Efforts to expand marketing through digital platforms such as Shopee have not produced optimal results due to limited promotion and a lack of human resources with digital marketing skills. The marketing strategy in this study is analyzed using the 7P marketing mix approach, which includes product, price, place, promotion, people, process, and physical evidence. The results indicate that strengthening strategies across these aspects is necessary, including improving product quality, adjusting pricing strategies, optimizing the use of social media for promotion, and providing marketing skill training for both inmates and officers. With more effective marketing strategies, Batik Jeruji has the potential to become more widely recognized by the community and to provide economic and social benefits for both the inmates and the correctional institution. Keywords: Batik Jeruji; Marketing; Inmate Welfare